2020
DOI: 10.1101/2020.09.05.284554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental plasticity of texture discrimination following early vision loss in the marsupialMonodelphis domestica

Abstract: Behavioral strategies that depend on sensory information are not immutable; rather they can be shaped by the specific sensory context in which animals develop. This behavioral plasticity depends on the remarkable capacity for the brain to reorganize in response to alterations in the sensory environment, particularly when changes in sensory input occur at an early age. To study this phenomenon, we utilize the short-tailed opossum, a marsupial that has been a valuable animal model to study developmental plastici… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 89 publications
(81 reference statements)
1
7
0
Order By: Relevance
“…Recent data from our laboratory indicate that EB animals are better at making fine tactile discriminations but show no differences in whisking behavior compared with SC opossums (Ramamurthy et al, Society for Neuroscience Abstracts, 2018; Ramamurthy and Krubitzer, 2018). In the current study, we found that EB opossums could detect rungs and place their limbs more accurately during ladder rung walking than SC opossums.…”
Section: Cross-modal Behavioral Plasticity Following Early Loss Of Visionsupporting
confidence: 50%
See 4 more Smart Citations
“…Recent data from our laboratory indicate that EB animals are better at making fine tactile discriminations but show no differences in whisking behavior compared with SC opossums (Ramamurthy et al, Society for Neuroscience Abstracts, 2018; Ramamurthy and Krubitzer, 2018). In the current study, we found that EB opossums could detect rungs and place their limbs more accurately during ladder rung walking than SC opossums.…”
Section: Cross-modal Behavioral Plasticity Following Early Loss Of Visionsupporting
confidence: 50%
“…It may also be possible that EB animals are more efficient in their acquisition of sensory information through differences in whisker movement. Previous data from our laboratory indicate this is not the case, as EB and SC Monodelphis have similar whisker set-points and whisking frequencies (Ramamurthy and Krubitzer, 2018). Research in functionally blind rats with similar results adds support for EB animals having heightened sensory coding versus heightened sensory acquisition (Arkley et al, 2014).…”
Section: Neural Mechanisms That May Subserve Adaptive Cross-modal Behavioral Plasticitymentioning
confidence: 62%
See 3 more Smart Citations